Pentingnya Pendidikan Seksual Anak Usia Dini - Ode Yahyu Herliany Yusuf; Muhammad Syukran; Melianti; Wa Ode Rahmadani; Hisna; Ainna Putri; Wa Ode Amira Fahrani; Satriwati (CV. Multi Kreasi Media, 2022)
Community service activities are activities that include efforts to improve the quality of human resources, knowledge and broaden horizons. Sex education is an effort to teach, raise awareness and provide information about sexual problems. The information provided includes knowledge about the function of the reproductive organs by instilling morals, ethics, commitment, religion so that